GROWTH AND SURVIVAL OF TROPICAL ABALONE Haliotis asinina SEED IN CONCRETE TANKS AT DIFFERENTS STOCKING DENSITY - Mat Sardi Hamzah; Sigit Anggoro Putro Dwiono; Safriyadi Hafid (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Tropical abalones (Haliotis asinina) is a marine gastropod that has high economic value and consumed by people in the world. In 2002, the production of abalones was 4.076 ton from total production of marine fisheries in the world 8.000 ton. The countries that produce abalone by farming are Taiwan, Cina, South Africa, Japan, Cilie, USA, Australia and New Zealand. Information about the production in Indonesia is scarce. The main issue faced by farmer is higher mortality during post larvae and juvenile. The aim of this research was to observe the influence of abalone seed density in concrete tanks regarding to growth and survival. The research was conducted in January - May 2012 Mataram Marine Bio Industry Technical Implementation Unit, LIPI. Analysis of varians showed that seed densities was not significantly different (P>0.05). The highest survival rate were in density 75 individual/tank with 11.11 % mortality. The highest growth rate were in 50 individual/tank with shell growth rate 0.21cm/14 days and seed weight was 1.23 g.Keywords: growth, survival rate, seed of abalone (Haliotis asinina), density